Investigation of the Possible Role of Tie2 Pathway and TEK Gene in Asthma and Allergic Conjunctivitis - Gál, Zsófia; Gézsi, András; Molnár, Viktor; Nagy, Adrienne; Kiss, András; Sultész, Monika; Csoma, Zsuzsanna; Tamási, Lilla; Gálffy, Gabriella; Bálint, Bálint L.; Póliska, Szilárd; Szalai, Csaba (Frontiers in Genetics, 2020)
Tie2, coded by the TEK gene, is a tyrosine kinase receptor and plays a central role in vascular stability. It was suggested that variations in the TEK gene might influence the susceptibility to asthma and allergic conjunctivitis. The aim of this study was to further investigate these suggestions, involving different populations and to study the Tie2 related pathway on a mouse model of asthma. The discovery, stage I cohort involved 306 patients with moderate and severe allergic rhinitis, the stage II study consisted of 4 cohorts, namely adult and pediatric asthmatics and corresponding controls. Altogether, there were 1258 unrelated individuals in these cohorts, out of which 63.9% were children and 36.1% were adults. In stage I, 112 SNPs were screened in the TEK gene of the patients in order to search for associations with asthma and allergic conjunctivitis. The top associated SNPs were selected for association studies on the replication cohorts. The rs3824410 SNP was nominally associated with a reduced risk of asthma in the stage I cohort and with severe asthma within the asthmatic population (p=0.009; OR=0.48) in the replication cohort. In the stage I study, 5 SNPs were selected in conjunctivitis. Due to the low number of adult patients with conjunctivitis, only children were involved in stage II. Within the asthmatic children, the rs622232 SNP was associated with conjunctivitis in boys in the dominant model (p=0.004; OR=4.76), while the rs7034505 showed association to conjunctivitis in girls (p=0.012; OR=2.42). In the lung of a mouse model of asthma, expression changes of 10 Tie2 pathway-related genes were evaluated at three points in time. Eighty percent of the selected genes showed significant changes in their expressions at least at one time point during the process, leading from sensitization to allergic airway inflammation. The expressions of both the Tek gene and its ligands showed a reduced level at all time points. In conclusion, our results provide additional proof that the Tie2 pathway, the TEK gene and its variations might have a role in asthma and allergic conjunctivitis. The gene and its associated pathways can be potential therapeutic targets in both diseases.